Association between hs-CRP and depressive symptoms: a cross-sectional study - Ji, Yewei; Wang, Jinmin; Chen, Huaqin; Li, Jiawen; Chen, Mingyang (Frontiers in Psychiatry, 2024)
Background and aim High-sensitivity C-reactive protein (hs-CRP) is a sensitive measure of low-grade inflammation and appears superior to conventional blood tests in assessing cardiovascular disease. The purpose of this investigation was to explore the link between high-sensitivity CRP and depressive symptoms among adults. Methods and results Multiple logistic regression and smoothed curve fitting were used to investigate the association between hs-CRP and depressive symptoms based on data from the, 2017-2020 National Health and Nutrition Examination Survey (NHANES). Subgroup analyses and interaction tests were used to assess the stability of this relationship across populations. The study comprised 6,293 non-clinical participants, which included 549 individuals with depressive symptoms. The prevalence of depressive symptoms was found to increase with increasing levels of hs-CRP. This trend persisted even after quartetting hs-CRP levels. In the fully adjusted model, each unit increase in hs-CRP was associated with a 10% increase in the odds of depressive symptoms (OR=1.10,95%CI:1.01-1.21). Participants in the highest quartile of hs-CRP had a 39% higher prevalence of depressive symptoms compared to those in the lowest quartile (OR=1.39,95%CI:1.01-1.92). Additionally, this positive correlation was more pronounced in men. Conclusions In adult Americans, there exists a positive association between elevated hs-CRP levels and depressive symptoms, with a more prominent manifestation of this association observed in males.